Eksistensi Pujian Himne “Mengikut Yesus Keputusanku” dan Perkembangan Musik Kontemporer pada Liturgi Ibadah Masa Kini - Jhonnedy Kolang Nauli Simatupang (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2023)
The purpose of this research is to see and provide an understanding of the existence of a hymn in the liturgy of Christian worship today, both hymns and contemporary hymns, and the meaning of the hymn "Mengikut Yesus Keputusanku." A qualitative research method is used through a literature review in writing this scientific work. The results of this research are as follows. First, as church music grows in the liturgy of worship, it can be noted that whether or not the hymns of hymns are a little less, added several church denominations are coming to comfortable with the use of contemporary praise in the liturgy of worship, second, the "Mengikut Yesus Keputusanku." Praise is one of the great testimonies of those who sing this praise, regardless of this praise, it is a form of faith that one believes in God to this day, even this praise continues to grow with various translations and insights. Third, the presence of contemporary music and the praise of hymns should be combined into God.